2004
DOI: 10.1016/j.neuron.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Dap160/Intersectin Scaffolds the Periactive Zone to Achieve High-Fidelity Endocytosis and Normal Synaptic Growth

Abstract: Dap160/Intersectin is a multidomain adaptor protein that colocalizes with endocytic machinery in the periactive zone at the Drosophila NMJ. We have generated severe loss-of-function mutations that eliminate Dap160 protein from the NMJ. dap160 mutant synapses have decreased levels of essential endocytic proteins, including dynamin, endophilin, synaptojanin, and AP180, while other markers of the active zone and periactive zone are generally unaltered. Functional analyses demonstrate that dap160 mutant synapses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
259
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(293 citation statements)
references
References 45 publications
32
259
1
1
Order By: Relevance
“…Intersectin proteins contain multiple protein-protein interaction domains, and they have been shown to bind proteins involved in processes such as actin remodeling, signal transduction, exocytosis, and endocytosis (Roos and Kelly, 1998;Koh et al, 2004;Marie et al, 2004;Martin et al, 2006;Evergren et al, 2007). The Drosophila orthologue of Intersectin, Dap160, is essential for viability, and it functions as an endocytic scaffolding protein at neuromuscular junctions (Koh et al, 2004;Marie et al, 2004). In mammals, which have two Intersectin homologues, there is evidence suggesting that an interaction between Intersectin and the E3 ubiquitin ligase Cbl is important for endocytosis and degradation of epidermal growth factor receptor (Martin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intersectin proteins contain multiple protein-protein interaction domains, and they have been shown to bind proteins involved in processes such as actin remodeling, signal transduction, exocytosis, and endocytosis (Roos and Kelly, 1998;Koh et al, 2004;Marie et al, 2004;Martin et al, 2006;Evergren et al, 2007). The Drosophila orthologue of Intersectin, Dap160, is essential for viability, and it functions as an endocytic scaffolding protein at neuromuscular junctions (Koh et al, 2004;Marie et al, 2004). In mammals, which have two Intersectin homologues, there is evidence suggesting that an interaction between Intersectin and the E3 ubiquitin ligase Cbl is important for endocytosis and degradation of epidermal growth factor receptor (Martin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Intersectin adaptor protein is thought to function in clathrin-dependent endocytosis by recruiting endocytosis machinery to clathrin-coated pits (Yamabhai et al, 1998;Sengar et al, 1999;Simpson et al, 1999;Koh et al, 2004;Marie et al, 2004). The C. elegans genome contains a single Intersectin orthologue, called ITSN-1, which is most similar to Drosophila dynamin-associated protein of 160 kDa (Dap160) and the short isoform of human ITSN1 ( Figure 5A).…”
Section: Unc-11 and Itsn-1 Function Upstream Of Lin-10 But Not Rab-10mentioning
confidence: 99%
“…A crucial part in synaptic vesicle endocytosis is played by the GTPase dynamin (FIG. 2), a mechanochemical enzyme recruited to endocytic sites by interaction with SH3 domain proteins 58,59 , including intersectin [60][61][62] , amphiphysin 63 , endophilin 64,65 and syndapin 66 , suggesting a tight interplay between BAR-SH3 protein-mediated membrane deformation (FIG. 2) and dynamin-catalyzed fission 58,67 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
“…Genetic studies have identified the multidomain endocytic scaffolding proteins intersectin [60][61][62]71 and epidermal growth factor receptor substrate 15 (EPS15) 72 as crucial for synaptic vesicle membrane retrieval and synapse development in Drosophila melanogaster and Caenorhabditis elegans. Expression levels of intersectin and EPS15 are interdependent, and the phenotypes observed on loss of either protein are nearly identical, indicating a close functional relationship between both proteins 72 .…”
Section: Box 1 | Presynaptic Organization -Exocytic and Endocytic Zonesmentioning
confidence: 99%
See 1 more Smart Citation